(untitled) (Anais do Congresso Brasileiro de Processo Coletivo e Cidadania, 2020)
The duty to substantiate judicial decisions is a constitutional guarantee provided for in Article 93, item IX of the Federal Constitution of 1988. However, for some time the Brazilian reality of those who deal with law in Brazil has been facing decisions lacking foundation and quality. , which consequently generates constant appeals and instability in the provision of the judicial service. With the advent of the New Code of Civil Procedure, the duty of motivation was reinforced through article 489, first paragraph, and also by introducing the theory of mandatory precedents provided for in article 927. In this context, we sought to analyze the main changes in civil procedural norms as to the duty of motivation and the importance of reasoning in court decisions for stability and efficiency in the delivery of jurisdiction. The method used for the development of the research was the deductive one, based on techniques of bibliographic data collection, documentary, via internet, among others.